Internet of things to controlling building electrical equipment - Muhammad Adam; Roslina; Suprianto; Mardiana (Institute of Computer Science (IOCS), 2023)
The use of electrical energy that is not used as needed will lead to wastage of electrical energy. Research on the application of the Internet of Things for controlling electrical equipment specifically for the electric load of lighting lamps on the first floor of Building C, the Department of Electrical Engineering, Medan State Polytechnic aims to implement an IoT system for controlling electric lighting with scheduling mode, remote control mode via internet network and light sensor mode. Thus controlling electrical equipment, in this case lighting, can be done easily through automation of the IoT system at any time and anywhere. The specific target to be achieved in this research is implementing an IoT system for controlling lighting electrical equipment in scheduling mode, remote control mode via the internet network and light sensor mode. The method used in this research is the experimental method, which collects data from observations and designs, which is then tested. The research output target is applied vocational products that are implemented in the Department of Electrical Engineering, Medan State Polytechnic. the equipment used is PZEM 004T Sensor, Photocell, RTC DS 3231, NodeMCu ESP 8266, Triac BT 136, MOC3021 Triac Driven Optoisolator, Contactor, Relay, Photocell, CT and other supporting equipment